Penguatan Literasi Keuangan Syariah sebagai Pilar Keberlanjutan UMKM di Sumbergempol - Sari, Citra Mulya; Huda, Qomarul; Tegar, Tegar (Politeknik Negeri Malang, 2024)
Effective financial management is one of the key factors for business sustainability, especially for MSMEs. However, many MSMEs in Sumbergempol, Tulungagung face challenges in developing a sharia-based financial plan. The main problems include a lack of understanding of sharia financial principles, such as riba, gharar, and maysir, as well as limited skills in budgeting and separating personal finances from business finances. To address these issues, the community service team from the Faculty of Islamic Economics and Business at UIN Sayyid Ali Rahmatullah Tulungagung conducted a